Pengaruh Suhu dan Waktu terhadap Yield dan Kemurnian Pupuk K2SO4 dari Abu Kulit Buah Kapuk dan Gipsum - Galu Murdikaningrum; kenny kencanawati (Universitas Insan Cendekia Mandiri, 2020)
Indonesia is one of the largest agricultural countries in the world, with the majority of the population working as farmers. Theagricultural industry certainly needs fertilizer to maintain quality, accelerate growth and provide nutrients for plants to grow well. To provide cheap potassium sulphate fertilizer, we conducted a study on